Konsep Pemikiran Pierre Bourdieu dan Relevansinya terhadap Pengembangan Budaya Akademik di Perguruan Tinggi - Wihardjo, Edy; Pranawukir, Iswahyu; Yusuff, Andinna Ananda; Setiawan, Mohammad Febry Saputra; Fardhoni, Fardhoni (INCARE, International Journal of Educational Resources, 2024)
College is an educational institution that has an important role in providing contributive discourse in social life. How the tradition of critical thinking, respecting pluralistic thinking, and trying to strengthen a multicultural society becomes an academic culture in the intellectual arena. In developing an academic culture, the academic community, in this case becomes an agent, with the appropriate capital and habitus, can change or achieve certain goals. So, to make this happen, analysis and practice are needed that support the development of academic culture. One of the roles of this research is to explain Pierre Bourdieu's thinking and its relevance to the development of academic culture in higher education. Of course, the academic culture in question is in accordance with the goals of each educational institution. Apart from providing Bourideu's perspective, this research also aims to explain the steps that must be taken by agents in an intellectual arena. This research uses a literature or library research method to understand Bourdieu's basic thought concepts related to academic culture. Finally, Bourdieu's concept of thought provides analysis and practices that must be carried out in developing an academic culture in higher education. And how to overcome the problems that occur in it.